Remarks on strongly precloseds functions in topological space - Caldas, Miguel; Jafari, Saeid (Pro Mathematica, 2009)
In this note, we present some of the basic properties of the classes of functions called strongly preclosed closed and pre-irresolute functions in topological spaces.